Stable control of the high-speeding magnetically suspended rotor based on extended state observer and two-degree freedom internal model control for control moment gyros with serious moving-gimbal effects. (October 2020) - Tang, Jiqiang; Wei, Tongkun; Lv, Qichao; Cui, Xu
For a magnetically suspended control moment gyro (MSCMG), which is an ideal attitude actuator for its large outputting control moment and fast response, the moving-gimbal effects due to the coupling between the moving gimbal and high-speeding rotor will make the magnetically suspended rotor (MSR) unstable. To improve control precision, both the dynamic model of MSR and the feedback linearization control are done to decouple tilting motion, and poles of the system are reconfigured to reduce control error. To suppress the varying disturbance moments caused by moving-gimbal effects, an extended state observer (ESO) is originally designed to estimate and compensate them timely and accurately. To improve system robustness, a two-degree freedom internal model control (2-DOF IMC) is researched to suppress model error. Compared with existing proportional integral derivative (PID) control method, simulations done on a single gimbal MSCMG with 200 N.m.s angular momentum indicated that this presented control method with ESO and 2-DOF IMC can suppress the moving-gimbal effects more effectively and make the rotor suspension more stable.